2011
DOI: 10.1186/1824-7288-37-13
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants in selecting childhood diarrhoea treatment options in Sub-Saharan Africa: A multilevel model

Abstract: BackgroundDiarrhoea disease which has been attributed to poverty constitutes a major cause of morbidity and mortality in children aged five and below in most low-and-middle income countries. This study sought to examine the contribution of individual and neighbourhood socio-economic characteristics to caregiver's treatment choices for managing childhood diarrhoea at household level in sub-Saharan Africa.MethodsMultilevel multinomial logistic regression analysis was applied to Demographic and Health Survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 34 publications
8
54
0
Order By: Relevance
“…This is inconsistent with two studies in South Africa that reported over 70% ORT use, 21,27 and is particularly disappointing in view of the enormous efforts that have been put in place over the years to promote the use of ORT as an initial remedy in the treatment of acute diarrhoea at home. [13][14][15]21,27,32,[37][38][39] It is possible that the poor uptake of ORT in this study may be in keeping with the reported widespread use of unconventional remedies to treat diarrhoea in some South African settings. 11,12,27 Although the study found that 4% of the participants used unconventional remedies, this small proportion may have been under-reported on account of mothers' hesitation to share information that might be criticised by the health system, especially when viewed against the backdrop of the well-documented use of traditional remedies, 11,12,14,15 antibiotics, 40,41 and anti-diarrheals 14 to treat diarrhoea in South Africa and elsewhere.…”
Section: Discussionmentioning
confidence: 82%
“…This is inconsistent with two studies in South Africa that reported over 70% ORT use, 21,27 and is particularly disappointing in view of the enormous efforts that have been put in place over the years to promote the use of ORT as an initial remedy in the treatment of acute diarrhoea at home. [13][14][15]21,27,32,[37][38][39] It is possible that the poor uptake of ORT in this study may be in keeping with the reported widespread use of unconventional remedies to treat diarrhoea in some South African settings. 11,12,27 Although the study found that 4% of the participants used unconventional remedies, this small proportion may have been under-reported on account of mothers' hesitation to share information that might be criticised by the health system, especially when viewed against the backdrop of the well-documented use of traditional remedies, 11,12,14,15 antibiotics, 40,41 and anti-diarrheals 14 to treat diarrhoea in South Africa and elsewhere.…”
Section: Discussionmentioning
confidence: 82%
“…This result suggests that situations of the community contexts where children are born or raised significantly influence under-five mortality in Nigeria. This underscores the need to take neighbourhood contexts into consideration (Aremu et al, 2011;Boco, 2010) in the efforts to address the high level of under-five mortality in the country.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the urban dwellers in the North Eastern parts of KNM are more likely to seek modern health care for diarrhoea as compared to the rural inhabitant of the KNM and the KNWD. This could be linked with high socio-economic status and educational levels of caregivers of children under five years in the North Eastern parts of the Municipality as compared to the other communities in the KNM and the KNWD as found in other studies [3,12]. In these two studies families with higher socio economic status had a greater chance of seeking orthodox health care for ailments including diarrhoea.…”
Section: Discussionmentioning
confidence: 68%
“…About 80% of these deaths occur in developing countries [1,2]. In sub-Saharan Africa, the incidence of diarrhoea has been linked with poverty as poor communities lack adequate sanitation and water supply [3]. Seasonality of diarrhoeal diseases have been reported by different authors worldwide [2,4].…”
Section: Introductionmentioning
confidence: 99%